The novel antitumor compound clinopodiside A induces cytotoxicity via autophagy mediated by the signaling of BLK and RasGRP2 in T24 bladder cancer cells - Zhou, Rong Sheng; Zhao, Ji Zhong; Guo, Li Ming; Guo, Jia Li; Makawy, Aida El; Li, Zong Yun; Lee, Shao Chin (Frontiers in Pharmacology, 2022)
In the study, we investigated the anti-cancer effect of clinopodiside A and the underlying mechanisms using T24 bladder cancer cells as an experimental model. We found that the compound inhibited the growth of the bladder cancer cells in vitro and in vivo in a dose-dependent manner, which showed a combinational effect when used together with cisplatin. In the bladder cancer cells, clinopodiside A caused autophagy, which was mediated by the signaling of BLK and RasGRP2, independently. Inhibition of the autophagy by chemical inhibitor 3-methyladenine or by the inhibition of the signaling molecules attenuated the cytotoxicity of clinopodiside A. Further analyses showed that clinopodiside A acted in synergism with cisplatin which itself could trigger both autophagy and apoptosis, which occurred with concomitant enhancements in autophagy and the cisplatin-evoked apoptosis. In conclusion, our results suggest that clinopodiside A inhibits the growth of the bladder cancer cells via BLK- and RasGRP2-mediated autophagy. The synergistic effect between clinopodiside A and cisplatin is attributed to the increases in autophagy and autophagy-promoted apoptosis. Clinopodiside A is a promising investigational drug for the treatment of cancer, at least blabber, which can be used alone or in combination with clinical drug(s).